2017
DOI: 10.1186/s13099-017-0165-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of Helicobacter pylori type IV secretion system components CagL and CagI and their association with clinical outcomes

Abstract: Background Helicobacter pylori infection is associated with risk for chronic gastritis (CG), gastric ulcer (GU), duodenal ulcer (DU), and gastric cancer (GC). The H. pylori Cag type IV secretion system (TFSS) translocates the virulence factor cytotoxin-associated gene A protein into host cells and plays an important role in initiating gastric carcinogenesis. The CagL and CagI proteins are components of the TFSS. The Arg-Gly-Asp (RGD) motif of CagL, and the six most distal C-terminal amino acids (Ser-Lys-Ile-Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
31
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 31 publications
11
31
5
Order By: Relevance
“…In the meantime, the most variable region in CagN amino acid sequence was found at residues 53 to 63, which includes many missense mutations and it is postulated to contain GDEEITEEEKK in the P12 reference strain. Our ndings revealed that there was no signi cant correlation between clinical outcomes and cagI and cagN variants at both nucleotide and amino acid levels (P > 0.05), which is in consistent with previous study reported by Ogawa et al [26]. Pham et al, stated that C-terminal motif (SKVIVK) in CagI is essential for T4SS function, and thus is completely conserved among H. pylori strains.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the meantime, the most variable region in CagN amino acid sequence was found at residues 53 to 63, which includes many missense mutations and it is postulated to contain GDEEITEEEKK in the P12 reference strain. Our ndings revealed that there was no signi cant correlation between clinical outcomes and cagI and cagN variants at both nucleotide and amino acid levels (P > 0.05), which is in consistent with previous study reported by Ogawa et al [26]. Pham et al, stated that C-terminal motif (SKVIVK) in CagI is essential for T4SS function, and thus is completely conserved among H. pylori strains.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with above mentioned study, our ndings also con rmed that the CagI C-terminal motif was completely conserved among all H. pylori isolates. Ogawa et al discovered complete RGD motifs in CagL sequences were observed from all isolates, which possibly imply the importance of the RGD motif for CagL function [26]. A recent investigation on this topic was performed by Yadegar et al in Iran, in which almost 97% of H. pylori clinical strains contained cagL gene [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous publications reported an association of GC with the presence of variants in position 58 and 59 of cagL protein; in two studies 35,36 the concurrent presence of tyrosine (Y) in amino acid position 58 and glutamic acid (E) in position 59 (Y58E59) compared with the combination aspartic acid (D58) and Lysine (K59), induced more efficiently a shift of gastric integrin a5b1 in the corpus, which has been related with gastric carcinogenesis. In our previous publication we did not observe the Y amino acid in position 58 in any sample, although we did find that carriers of D at this position are at lower risk of GC in comparison with the asparagine (N) carriers 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular the cagL S10F variant (located at codon 10) changes from serine (polar) to phenylalanine (non-polar). Interestingly, among the 43 Asian strains recently sequenced, no single S10F variant was found, suggesting that this is a Western-strain specific variant 35 . Thus, overall, the differences observed in these studies are likely to be driven by geographical origins of HP.…”
Section: Discussionmentioning
confidence: 99%